Lipopolysaccharide- and Cholera Toxin-Specific Subclass Distribution of B-Cell Responses in Cholera - Qadri, Firdausi (American Society for Microbiology, 1999)
The immunoglobulin subclass responses to homologous lipopolysaccharide (LPS) and to cholera toxin (CT) in adult patients infected with Vibrio cholerae O1 and V. cholerae O139 were studied. LPS-specific antibody-secreting cells (ASC) of both the immunoglobulin A1 (IgA1) and IgA2 subclasses were seen, with the IgA1 ASC response predominating in both V. cholerae O1- and O139-infected patients. For antibodies in plasma, by day 11 after onset of disease, all V. cholerae O1- infected patients responded to homologous LPS with the IgA1 subclass (P = 0.001), whereas fewer (68%) responded with the IgA2 subclass (P = 0.007). About 89% of V. cholerae O139-infected patients responded with the IgA1 subclass (P = 0.003), and only 21% responded with the IgA2 subclass (not significant [NS]). Both groups of cholera patients showed significant increases in LPS-specific IgG1, IgG2, and IgG3 antibodies in plasma. In feces, the response to homologous LPS occurred in both groups of patients with the IgA1 and IgA2 subclasses, with 55 to 67% of patients showing a positive response. V. cholerae O1- and O139-infected patients showed CT-specific ASC responses of the different IgG and IgA subclasses in the circulation, and the pattern followed the order IgG1 > IgA1 > IgG2 > IgA2, with low levels of IgG3 and IgG4 ASC. Plasma anti-CT antibody responses in all subclasses were seen by day 11 after onset of disease. Although there were no increases in CT-specific ASC of the IgG3 (NS) and IgG4 (NS) subtypes, there were significant increases of these two subclasses in plasma (P ≤ 0.001). The response to CT in the fecal extracts was contributed to by both IgA1 and IgA2 isotypes, with 67 to 75% of the patients responding. Thus, the mucosa-derived ASC and fecal antibodies to LPS and CT were of both the IgA1 and IgA2 subclasses; in plasma, the contribution from IgA2 was lower. Very little difference in the B-cell responses to LPS and CT in the different subclasses was seen in the two groups of cholera patients. Vaccines against O1 and O139 cholera ideally should stimulate antibody subclasses that are likely to offer protection.